Reinventing Grammar Pedagogy through Mobile-Assisted Learning: Busuu-Assisted Tense Mastery in an Indonesian Madrasah Tsanawiyah - Sepia, Sepia; Kalsum, Kalsum; Haris Sunubi, Abdul; Munawir, Munawir (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This research addresses the persistent challenge of tense instruction in Indonesian madrasah tsanawiyah, where grammar learning is often perceived as rule-heavy and detached from meaningful practice. The study aims to examine the extent to which Busuu-assisted learning can enhance eighth-grade students’ English tense mastery and to outline a feasible classroom integration model within a realistic school timetable. A pre-experimental one-group pre-test–post-test design was employed with qualitative approach. The participants were 23 eighth-grade students at MTs DDI Tuppu Pinrang selected from an intact class; however, complete matched pre- and post-test scores were available for 22 students and were used for analysis. Students completed a 30-item multiple-choice grammar test on simple present, simple past, and simple future tenses before and after six weekly Busuu-assisted treatments (two class periods per meeting). Data were analyzed using descriptive statistics and a paired comparison, applying the Wilcoxon signed-rank test due to non-normal gain scores. The results showed a substantial increase in students’ tense mastery from pre-test (M = 20.18) to post-test (M = 28.23), with a significant pre–post difference (p < .001) and a very large effect (r ≈ 0.88). The findings suggest that structured mobile-assisted practice through Busuu, combined with teacher guidance and error-focused review, can serve as a practical strategy for revitalizing grammar pedagogy in Islamic junior high school contexts.